THE DETERMINANT CHOICE AS AN ACCOUNTANT WITH INFORMATION TECHNOLOGY AS A MODERATING VARIABLE - Heriska Sri Kresna; Ikhsan Budi Riharjo; Fidiana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to investigate the influence of the job market and compensation on students’ decisions to pursue a career as an accountant, with information technology serving as a moderating variable. A quantitative research approach was employed. The study population includes all undergraduate accounting students at STIESIA Surabaya. Data were collected using probability sampling through a simple random sampling method. This study utilized multiple linear regression along with Moderated Regression Analysis (MRA) to examine interaction effects. The study's findings demonstrate that job market factors have a significant positive effect on individuals' decisions to enter the accounting profession. Likewise, financial rewards also play a crucial role by exerting a positive and significant influence on career selection. Likewise, professional recognition positively and significantly affects students’ inclination to become accountants. However, information technology moderates this relationship by weakening the influence of financial rewards on career choice. In contrast, it enhances the effect of professional recognition on the decision to pursue an accounting career.